Albendazole in the treatment of pulmonary echinococcosis. Issue 8 (August 1991) - Aggarwal, P; Wali, J P
Abstract : Ten patients with pulmonary hydatid disease diagnosed on the basis of a chest radiograph and a positive response to the indirect haemagglutination test for hydatid disease were treated with albendazole 10 mg/kg/day for eight weeks. None of the 10 patients showed any radiological or serological improvement with this treatment regimen. Albendazole in these doses appears to have little role in the treatment of pulmonary hydatid disease.